Atividades antioxidante, anti-inflamatória e cicatrizante do caju (Anacardium occidentale L.) - Vasconcelos, Mirele da Silveira (2011)
Anacardium occidentale L. (Anacardiaceae), known as cashew, is a typical tropical pseudo whose juice is highly consumed in Brazil for its excellent sensory and nutritional properties. The aim of this study was to evaluate the antioxidant, anti-inflammatory and wound healing activities of cashew apple in vitro and in vivo. The juice from fresh fruit were obtained from cashew clones CCP 76 in the maturation stage 2 (unripe) and 6 (ripe). Were determined in the juice total polyphenols, vitamin C, anthocyanins, flavanols, carotenoids, phenolic compounds and the total antioxidant activity. For the evaluation of anti-inflammatory activity and healing in vivo was performed in mice, kept under appropriate conditions of light, temperature and given water and food ad libitum. The experimental protocol was approved by the Ethics Committee for Animal Experiments of the UFC (nº 85/09). To evaluate the effect of oral treatment for 30 consecutive days with the juice of cashew apple ripe and unripe, we used the methodology of the ear edema induced by xylene. Regarding the effect of treatment with the juice of cashew in the healing lesions were induced on the backs of mice 15 days after initiation of treatment. The skin lesions by morphometric and macroscopic analysis were subjected to clinical evaluation for 21 days. Results were expressed as mean and standard deviation. To evaluate the significant differences between the means of different groups, we applied the Mann-Whitney test and ANOVA and differences were considered significant when p <0.05. The ripe cashew apple juice (RCAJ) phytochemistry profile was better with levels of non-enzymatic antioxidants and total antioxidant capacity than the unripe cashew apple juice (UNCAJ). The anti-inflammatory and healing results showed that the UNCAJ reduced inflammation and accelerated wound healing process when compared to RCAJ. The present study demonstrated that the UNCAJ present high biological activity in inflammatory and wound healing models than the RCAJ.